BODY IMAGE SISWA-SISWI YANG MENGALAMI OBESITAS DI SMA NEGERI 8 DENPASAR - Windu Astutik; Gusti Ayu Ratih Kusuma Wardani (Coping: Community of Publishing in Nursing, 2020)
Adolescence is a period in a period of growth and processes of maturity man. Obesity is a condition in which the amass excess body fat, so weight someone is way up to normal limits. Prevalence of obesity in the city Denpasar of 10,5 % or as many as 11.730 people with of men 5.371 people and women 6.359 one. Body image is a collection of an individual to his body of perception past and present, road structure and feeling about, form, and bodily functions. The research aims to understand a body image in obesity in the state SMAN 8 Denpasar. Population in this study in obesity and take the subject of study uses the technique of sampling total of sampling as many as 63 one. The instrument used is the body of this multi-dimensional selfrelations questionnaire (MBSRQ). The result of this research got that respondents obesity that experienced the body image positif as many as 59 people (93.6 %) and suffered from the body image negatif as much as four people (6.4%). It can be concluded that the majority of respondents in SMAN 8 Denpasar having a positif body image.